Graduates employability in Malaysia: analysing student level of study and field of study in relation to their employability - Ali @ Hamid, Mass Hareeza; Ali, Anees Janee; Ali, Sufaid; Ibrahim, Muhammad Fithri; Bi, Fangling; Ahmed, Zubair; Abdullahi, Ndagi (International Journal of Academic Research in Progressive, 2024)
This study analyzes the employability trends of graduates from Malaysian higher education institutions, with a focus on bachelor’s, master’s, and doctoral degree holders. Using data from the Ministry of Higher Education (MOHE), the study examines graduate employability across different types of education and fields of study by using the Python analysis. The findings reveal that while bachelor’s degree graduates exhibit lower employability rates, averaging around 30%, master’s and PhD graduates show significantly higher employability, with PhD programs achieving a 100% employment rate. The study also highlights that fields such as Applied Arts, including accountancy and business-related disciplines, demonstrate the highest graduate employability. The Kernel Density Estimation (KDE) analysis confirms a positive relationship between institutional type, level of education, and field of study, with an R² score of 0.83. Despite overall high employability rates, certain variables negatively influence graduate outcomes, signaling areas for further investigation. This research provides valuable insights for stakeholders to address graduate unemployment and improve alignment between tertiary education and labor market demands.